Happy birthday, Felicity! : a springtime story - Tripp, Valerie, 1951- (American girls collection, 1992)
As her tenth birthday approaches, Felicity is excited by her grandfather's visit, but she is also concerned about the growing tensions between the colonists and the British governor in Williamsburg.